Mediation in international economic relations – different approaches and cultural background - Broszkiewicz, Magdalena (Mediacja w międzynarodowych stosunkach gospodarczych – zróżnicowane podejścia i uwarunkowania kulturowe, 2018)
In the globalising world, similar phenomena are spreading in the world economy, politics, demography, social life and culture, regardless of the geographical context and the level of economic development of a given region. There are disputes over economic, political or social background that concern citizens of different countries. Also the mediation procedure is popularized, which facilitates the diffusion of a new approach to conflicts. The subject of this article is to present a contemporary image of mediation, with particular emphasis on cross-border mediation, as well as their history and indication of the most-important functions in societies and their potentially high significance in the future. The main purpose of the article is to present cross-border mediation as the best way to resolve conflicts between representatives of different countries, nations, cultures, etc., as well as to draw attention to the barriers related to their application
Ekonomia XXI Wieku = Economics of the 21st Century, 2018, Nr 3 (19), s. 98-109
Keywords: mediation; international economic relations; cultural background of economy; mediacja; międzynarodowe stosunki gospodarcze; uwarunkowania kulturowe